Monitoring structural defects and crystallinity of carbon nanotubes in thin films - Mahajan, S. S.; Bambole, M. D.; Gokhale, S. P.; Gaikwad, A. B. (Pramana-Journal of Physics, 2010)
We report the influence of catalyst formulation and reaction temperature on the formation of carbon nanotube (CNT) thin films by the chemical vapour deposition (CVD) method. Thin films of CNTs were grown on Fe-Mo/Al(2)O(3)-coated silicon wafer by thermal decomposition of methane at different temperatures ranging from 800 to 1000A degrees C. The electron microscopic investigations, SEM as well as HRTEM, of the as-grown CNT thin films revealed the growth of uniform multi-walled CNTs in abundance. The intensity ratio of D-band to G-band and FWHM of G-band through Raman measurements clearly indicated the dependency of structural defects and crystallinity of CNTs in thin films on the catalyst formulation and CVD growth temperature. The results suggest that thin films of multi-walled CNTs with negligible amount of defects in the nanotube structure and very high crystallinity can be obtained by thermal CVD process at 925A degrees C.
Keywords: Carbon nanotubes; chemical vapour deposition; Raman spectroscopy; scanning electron microscopy; Thin films

Oxidative dehydrogenation of ethylbenzene using nitrous oxide over vanadia-magnesia catalysts - Shiju, N. Raveendran; Anilkumar, Mettu; Gokhale, S. P.; Rao, B. Seshagiri; Satyanarayana, C. V. V. (Catalysis Science & Technology, 2011)
A series of V-Mg-O catalysts with different loadings of vanadia were prepared by the wet impregnation method and the effect of the local structure of these catalysts on the oxidative dehydrogenation of ethylbenzene with N(2)O was investigated. High styrene selectivity (similar to 97%) was obtained at 773 K. The characterization of catalysts with methods such as XRD, FTIR, UV-visible, TPR, NMR and Laser Raman spectroscopy suggested that magnesium orthovanadate is the predominant vanadium containing phase and the size of the orthovanadate domains increases with increasing vanadia loading. The rate of ODH of ethylbenzene per V atom increases with vanadia loading and reaches a maximum at 10 wt%. The specific activity, i.e. the conversion of ethylbenzene per unit surface area of the catalysts, also exhibited a maximum at a vanadia loading of 10 wt% leading to the conclusion that activity of these catalysts is due to the presence of very small domains of Mg(3)(VO(4))(2) on the surface of MgO rather than crystallites of bulk Mg(3)(VO(4))(2). The higher styrene yield in the presence of N(2)O can be ascribed to the ability of N(2)O to keep vanadium species at a higher oxidation state.

Enhanced photocatalytic activity of multi-doped TiO2 for the degradation of methyl orange - Charanpahari, A.; Umare, S. S.; Gokhale, S. P.; Sudarsan, V.; Sreedhar, B.; Sasikala, R. (Applied Catalysis A-General, 2012)
We report the synergistic effect of dopants like Gd, N and Sin enhancing the photocatalytic activity of TiO2. Nanosized TiO2 doped at both cationic and anionic sites by Gd, N and S exhibited increased photocatalytic activity compared to TiO2 doped with either Gd or N and S. All the doped TiO2 existed as anatase phase and no separate phase due to Gd2O3 was seen up to a Gd concentration of 2%. The particle size as seen from the transmission electron micrograph was similar to 25 nm. The optical absorption property of TiO2 was improved by doping and redshift of the absorption edge is seen for all doped samples compared to pristine TiO2. The red shift of the absorption edge was the highest for the multiple ion-doped sample. Presence of bonded N and S in TiO2 was detected by X-ray photoelectron spectroscopy. Fluorescence lifetime studies indicated an enhanced lifetime for the charge carriers in the doped system compared to pristine TiO2. Photocatalytic activity study showed that the multi-doped sample has the highest activity for the degradation of methyl orange compared to Gd-TiO2, NS-TiO2 and pristine TiO2. The enhanced photocatalytic activity of the multi-doped TiO2 is attributed to factors such as improved optical absorption property and improved lifetime of the charge carriers. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Fluorescence lifetime; Gd N S doped TiO2; Methyl orange; Photocatalyst; Photodegradation